2014
DOI: 10.1002/ccd.25765
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the occurrence of new conduction abnormalities after transcatheter aortic valve implantation

Abstract: Over time the frequency of LBBB after TAVI decreased significantly, especially in patients undergoing TAVI with the MCS. Experience and the subsequent reduction in depth of implantation seem responsible for this reduction. Contrary to TAVI-LBBB, the incidence of PPI remained unchanged over time and was not affected by experience. Although experience has led to a decrease in new CAs after TAVI, elucidation of pathophysiologic mechanisms underlying these CAs and subsequent changes in patient stratification, valv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 43 publications
2
19
0
5
Order By: Relevance
“…The markedly higher PPMIR reported for the self-expanding CoreValve (Medtronic, Minneapolis, Minnesota) (range, 24% to 33%) (10) was suggested to be caused by the design-related extension of the stent deeper into the left ventricular outflow tract (LVOT) (8). Higher implantation of the valve was indeed reported to reduce the PPMIR (16). The longer stent of the S3 that may extend deeper into the LVOT may also result in a higher rate of AVCAs compared with the previous valve generation.…”
mentioning
confidence: 91%
“…The markedly higher PPMIR reported for the self-expanding CoreValve (Medtronic, Minneapolis, Minnesota) (range, 24% to 33%) (10) was suggested to be caused by the design-related extension of the stent deeper into the left ventricular outflow tract (LVOT) (8). Higher implantation of the valve was indeed reported to reduce the PPMIR (16). The longer stent of the S3 that may extend deeper into the LVOT may also result in a higher rate of AVCAs compared with the previous valve generation.…”
mentioning
confidence: 91%
“…Factors that predispose patients to TAVR-related PPM include right bundle branch block or left anterior fascicular block at baseline, smaller left ventricular outflow tract diameter, valve oversizing, a higher ratio of annulus diameter to left ventricular outflow tract diameter, depth of the prosthesis in the left ventricular outflow tract, severe mitral annular calcification, and calcification of either the left ventricular outflow tract or left or right coronary cusp. 5,13,[18][19][20][21][22] Although both LBBB and the need for PPM have been reported at higher rates with self-expanding valves compared to balloon-expandable valves, 11,18,23 the gap in post-TAVR PPM is narrowing with the newest generation of commercially available balloon-expandable and self-expanding valves. 22 In our study, new onset of persistent LBBB or worsening of LBBB was not associated with mortality at 1 year, with event rates too low to draw statistical conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have stated that cardiac CD is associated with longer QRS, SEV implantation, diabetes mellitus, post dilatation, and ID. [19][20][21][22] However, the relationship between MS length and the incidence of PPM implantation following TAVR with BEV is still controversial. 9,10 Oestreich et al showed that mean MS length was 7.5 mm in all their study subjects and no difference was observed between those with (7.9 mm) and without CD (7.2 mm); 9 however, Maeno et al indicated that a significant difference was seen in the mean MS length in patients requiring PPM (6.4 mm) and in those who did not require PPM (7.7 mm).…”
Section: Ms Length As Risk Factor For CD In Bev Patientsmentioning
confidence: 99%